Biosorption studies of nickel on Parthenium hysterophorous ash - Singh R.S.; Singh V.K.; Tiwari P.N.; Singh J.K.; Sharma Y.C. (My University, 2025)
The application of an aquatic weed, Parthenium hysterophorous, has been investigated for the removal of nickel from aqueous solutions. Parthenium hysterophorous, the weed was converted to ash and was used as an adsorbent for the removal of nickel(II) from aqueous solutions at different experimental conditions. The per cent removal of Ni increased from 67.30 to 97.54%, with the nickel(II) concentration decreasing from 477.21 to 67.83 mg L-1 at 25 C, pH 11.0. The removal was favoured at higher pH, with a maximum removal at pH 11.0. The effects of concentration and temperature are also reported. Batch adsorption kinetics are described by the Lagergren equation. The value of the rate constant of adsorption was found to be 6.82 10-2 min-1 at 67.83 mg L-1 and 25 C. The applicability of the Langmuir and Freundlich equations for the present system were tested at different temperatures, viz. 25, 50 and 75 C, and the constants were calculated. Thermodynamic parameters indicate the exothermic nature of nickel(II) adsorption on P. hysterophorous ash. The adsorption capacity was found to be much better than other common adsorbents reported for the removal of nickel(II).